European Journal of Remote Sensing - European Journal of Remote Sensing (Taylor & Francis, 2026)
Publishes research on active or passive remote sensing of terrestrial, oceanic, and atmospheric environments; drones; sensor systems and imaging.
FI 0.73
Q2
Keywords: Earth; Space & Environmental Sciences; Percepción remota; Acuerdos transformativos; Transformative agreements; Geología; Agricultura; Ecología; Hidrología; Oceanografía; Atmósfera; Meteorología